Analysis of the Implementation of the Mining Safety Management System at the Andesite Quarry in the Stone Crushing Area - Dimas Tidar Febrian; Heldi; Nurhasan Syah; Mulya Gusman (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyse the implementation of the Mining Safety Management System (SMKP) in the andesite quarry crushing area of PT. X, Subang Regency, West Java. The study uses a descriptive mixed methods approach that combines direct observation, structured interviews, and questionnaire surveys of workers in the crusher area using purposive sampling. The data were analysed using the Miles & Huberman model for qualitative data and descriptive statistics for quantitative data, with triangulation for validation of the results. The results showed that the implementation of SMKP at PT. X was still suboptimal. The overall criterion fulfilment rate reached 54.74% of the maximum total of 292 points, with significant variations between elements. The implementation element showed the best performance (54.31%), followed by organisation and personnel (54.55%), and monitoring and evaluation (60.42%). Conversely, three critical elements showed alarming conditions: documentation (33.33%), planning (37.93%), and management review (46.15%). This imbalance indicates a weak strategic planning system, procedural documentation, and continuous evaluation by top management. The study concluded that PT. X requires comprehensive and systematic improvements, prioritising documentation, safety programme planning, and management review to build the foundation of an effective mining safety management system in accordance with the regulations of the Ministry of Energy and Mineral Resources.